2018
DOI: 10.20944/preprints201807.0195.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Total Vertex-Edge Domination

Abstract: A novel domination invariant defined by Boutrig and Chellali in the recent: total vertex-edge domination. In this paper we obtain an improved upper bound of total vertex edge-domination number of a tree. If is a connected tree with order , then ( ) ≤ 3 ⁄ with = 6⌈ 6 ⁄ ⌉ and we characterize the trees attaining this upper bound. Furthermore we provide a characterization of trees with ( ) = ( ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…They also gave the relationship between and , , for trees and graphs, and also gave formulas to determine the double ev-domination number of paths and cycles. Sahin and Sahin [13] proved that the total ev-dominating set problem is NP-hard for bipartite graphs. They also showed that ( − + 2 − 1)∕2 is the upper bound for for a tree  with order , leaves and supporting vertices.…”
Section: Related Workmentioning
confidence: 99%
“…They also gave the relationship between and , , for trees and graphs, and also gave formulas to determine the double ev-domination number of paths and cycles. Sahin and Sahin [13] proved that the total ev-dominating set problem is NP-hard for bipartite graphs. They also showed that ( − + 2 − 1)∕2 is the upper bound for for a tree  with order , leaves and supporting vertices.…”
Section: Related Workmentioning
confidence: 99%
“…Graph theory was firstly proposed by Euler in 1736 [4]. Recently, the theory has been successfully applied to areas in different disciplines [9,10,11]. Since the theory is based on relational combinations, it has essential role in representing combinatorial objects and mathematical combinations.…”
Section: Introductionmentioning
confidence: 99%
“…e symbol c t ve (G) indicates the total ve-domination number of a graph G and c t ve (G) is equal to the minimum cardinality of a TVEDS. e total edge-vertex domination was presented in [14]. A subset B ⊆ E is a total edge-vertex dominating set (simply, TEVDS) of G, provided that B is an EVDS and every edge in B shares an endpoint with another edge in B. e symbol c t ev (G) indicates the total ev-domination number of a graph G and c t ev (G) is equal to the minimum cardinality of a TEVDS.…”
Section: Introductionmentioning
confidence: 99%